Health benefits of exercise and dietary interventions for patients with psoriasis – a literature review - Staniszewska, Izabela (Journal of Education, Health and Sport, 2024)
Introduction: Psoriasis is a prevalent chronic inflammatory systemic disease that can manifest in a variety of clinical manifestations. Psoriasis was thought to only affect the skin. Recent findings from dermatologic, rheumatologic, and cardiologic research indicate that it is a systemic disease, henceforth referred to as psoriatic disease. Purpose of work: Collecting information on the benefits of physical activity and diet modifications in patients with psoriasis on aspects such as metabolic syndrome, cardiovascular risk, mental health, and general well-being. Summary: Psoriasis is a disease that affects many areas of life. Physical activity improves the body weight, mental health, and cardiovascular risk of patients with psoriasis. Engaging in physical activity may reduce the probability of developing psoriasis and may also ameliorate its course. The Mediterranean diet, ketogenic diet, probiotics, and alcohol withdrawal may also alleviate the course of psoriasis. It is noteworthy to mention the potential limitations that may arise in the context of this disease, including embarrassment resulting from skin lesions and joint discomfort resulting from psoriatic arthritis. Sports training ought to be customized for each patient, taking into account their limitations and preferences.